Children's illustrated atlas - Brooks, Andrew (Lecturer in development geography) (DK Publishing, 2023)
"Set off on a globe-trotting adventure with this incredible atlas, which is bursting with colorful countries and continents, people and places, deserts and rain forests. From freezing Antarctica to the lush, green rain forests of Brazil and the hot, dry deserts of Africa, there's an amazing world out there just waiting to be discovered!" --